Asthma education and quality of life in the community: a randomised controlled study to evaluate the impact on white European and Indian subcontinent ethnic groups from socioeconomically deprived areas in Birmingham, UK. Issue 3 (1st March 2000) - Moudgil, H; Marshall, T; Honeybourne, D
Abstract : BACKGROUND: Whether asthma morbidity in minority groups can be reduced by preventative health care measures delivered in the relevant ethnic dialects requires further evaluation. This study reports clinical outcomes and quality of life from a community based project investigating white European (W/E) and Indian subcontinent (ISC) ethnic groups with asthma living in deprived inner city areas of Birmingham, UK. METHODS: Six hundred and eighty nine asthmatic subjects (345 W/E, 344 ISC) of mean (SD) age 34.5 (15) years (range 11–59) and mean forced expiratory volume in one second (FEV1 ) of 80% predicted were interviewed in English, Punjabi, Hindi, or Urdu. Subjects randomised to the active limb of a prospective, open, randomised, controlled, parallel group, 12 month follow up study underwent individually based asthma education and optimisation of drug therapy with four monthly follow up (active intervention). Control groups were seen only at the beginning and end of the study. Urgent or emergency interactions with primary and secondary health care (clinical outcomes) and both cross sectional and longitudinal data from an Asthma Quality of Life Questionnaire (AQLQ) were analysed. RESULTS: Clinical outcomes were available for 593 subjects. Fewer of the active intervention group consulted their GP (41.8% versus 57.8%, odds ratio (OR) 0.52 (95% CI 0.37 to 0.74)) or were prescribed antibiotics (34.9% versus 51.2%, OR 0.51 (95% CI 0.36 to 0.72)), but by ethnicity statistically significant changes occurred only in the W/E group with fewer also attending A&E departments and requiring urgent home visits. Active intervention reduced the number of hospital admissions (10 versus 30), GP consultations (341 versus 476), prescriptions of rescue oral steroids (92 versus 177), and antibiotics (220 versus 340), but again significant improvements by ethnicity only occurred in the active W/E group. AQLQ scores were negatively skewed to the higher values; regression analysis showed that lower values were associated with ISC ethnicity. Longitudinal changes (for 522 subjects) in the mean AQLQ scores were small but statistically significant for both ethnic groups, with scores improving in the active and worsening in the control groups. CONCLUSIONS: Active intervention only improved clinical outcomes in the W/E group. AQLQ scores, although lower in the ISC group, were improved by active intervention in both ethnic groups.